MAINTENANCE ANALYSIS OF ANCHOR CHAIN AGAINST CORROSION RATE BY PAINTING METHOD - Maulana Noor, Fariz; Rulianto, Rizal (IJMEA Journal Kedokteran Gigi, 2024)
One of the damages to the anchor and its chain is caused by being exposed to various environmental loads from the sea every time the anchor is lowered or when the anchor is raised, so that gradually it will experience fatigue or fatigue due to dynamic loads that occur repeatedly in a long period of time.However, there has not been an analysis that combines anchor chain maintenance of the corrosion rate with the painting method and comparison between before painting and after painting. Therefore, the researchers proposed a study "Analysis of Anchor Chain Maintenance of Corrosion Rates Using the Painting Method". This study aims to carry out an analysis to reduce the corrosion factor on the anchor chain by using marine coatings or painting processes, so that the operability and capability of the system can be maintained. The research design is based on an experimental method that seeks to posit and solve the problem of the condition of a ship's anchor chain made of steel or metal. based on both visual data and literacy. The existing data, then analyzed and interpreted, which is comparative. The interval for each coat of paint depends on the drying power. What can you do with the next coat of paint if the previous paint layer is dry, but it should not exceed the specified paint allowance, because it will give poor adhesion. From the analysis of the anchor chain structure, the resulting stress is 168.73 MPa, if it is estimated with a period of 3 years from the anchor chain structure, the stress result is 192.75 MPa, and if it occurs at this time in 2022 with a period of 5 years, the stress result is 213.95 MPa .